Caracterização dos sinais de desatenção e hiperatividade ao longo do desenvolvimento do adulto - Paes, Izabella Trinta (2018)
Attention Deficit Hyperactivity Disorder (ADHD) is a condition that begins in childhood, can persist into adult life, and can cause harm to various areas of life. Although the characteristics of the condition at this stage are already the subject of study in many studies, questions remain open, especially about the condition in adults with more advanced ages. Expanding this knowledge is relevant to conducting diagnostic and interventional practices. This study aimed to characterize from the cognitive and behavioral point of view the complaints of inattention and hyperactivity/impulsivity throughout adult development. Based on pre-determined indicators, he proposed describing changes throughout development, presenting associations with severity / frequency of ADHD complaints and describing differences with increasing age. Indicators of cognitive functioning (attention, cognitive flexibility, inhibitory control and working memory) and behavioral indicators of inattention and hyperactivity / impulsivity, functional impairments, levels of impulsivity, anxiety and depression, somatic complaints, thought problems and personal strengths were considered. To evaluate the indicators were used: Psychological Battery for Attention Assessment (BPA), Five Digit Test (FDT), Working Memory Index Wechsler Adult Intelligence Scale-Third Edition (WMI-WAIS-III), Diagnostic Interview for ADHD in adults (DIVA 2.0), Barratt Impulsiveness Scale (BIS 11), Functional Impairment Scale ADHD (EPF-ADHD) and Adult Self-Report Inventories (ASR / OASR). Participants included 68 volunteers between 18 and 68 years of age, and 49 of them between 20 and 68 years old were included in the sample analyzed. To this end, the Adult Self-Report Scale (ASRS 18), Mini Mental State Examination (MMSE), WASI and Personal Data Sheet and Anamnesis identified individuals with complaints of ADHD, without cognitive impairment suggestive of dementia, with adequate intellectual abilities, without current or life diagnosis of neurological and / or psychiatric conditions and without visual or auditory sensorial impairment. The analyzed sample was divided into two groups. Group 1, with 25 people between 20 and 30 years of age, and group 2, with 24 people between 31 and 68 years of age. Finally, Pearson's correlation analyzes and comparison analyzes were made through the Student's T-Test. The increase in ADHD complaints showed associations with: decline in personal strength; increased functional impairment (academic, domestic, financial and social); increased level of impulsivity; increase of indicators of Anxiety, Depression, somatic complaints and thought problems; decline in working memory performance; declining performance in concentrated and divided attention, and increased errors and omissions in tasks of concentrated, divided and alternate attention; and increased execution times due to inhibition and cognitive flexibility interference. With the increase of the age occurred: improvement in the performances in working memory; decline in performance in concentrated, divided and alternate attention; increased level of impulsivity; increased functional impairment (financial and transit); decline of indicators of Anxiety, Depression, somatic complaints and thought problems; and increased indicators of personal strength. With the increase of the age group there were no differences in inhibition, cognitive flexibility and number of ADHD complaints. These findings demonstrated the possible association between development and presentation of ADHD signs. The set of data found follows the same sense of the heterogeneity model in the characterization of the table. The study also ratified the importance of neuropsychological and behavioral assessment in diagnostic processes.